Therapeutic Potential of Bovine Lactoferrin to Reduce Brain Malondialdehyde Levels in Hyperlipidemia-Induced Sprague-Dawley Rats - Havian Daulung Telium; Tena Djuartina; Dion Notario; Linawati Hananta (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2024)
Hyperlipidemia is a medical condition that can trigger various diseases, one of which is a neurodegenerative or neurological disease. Lactoferrin is known to have multiple protective activities, one of which is antioxidant. This study aimed to determine the potential of lactoferrin bovine to decrease brain MDA levels in Sprague-Dawley (SD) rats induced by hyperlipidemia. This study was an in vivo experimental study using 24 male SD rats divided into six groups: normal, negative control, positive control, low-dose bovine lactoferrin (LLF), intermediate-dose bovine lactoferrin (ILF), and high-dose bovine lactoferrin (HLF). The diet in the normal group was the standard diet, and the other groups were induced by a high-fat diet (HFD). The intervention for the positive control group was simvastatin. In contrast, LLF, ILF, and HLF groups were given bovine lactoferrin doses of 100, 200, and 400 mg/kgBW, respectively. After seven weeks, all rats were necropsied, and their brains were taken to be tested for malondialdehyde (MDA) levels with an MDA assay kit using a spectrophotometer. Data was then analyzed using Shapiro-Wilk and Levene test and continued with one-way ANOVA and post-hoc Tukey test. There were significant differences (p<0.05) between the negative control group (269.99±13.50 nmol/g weight) and every bovine lactoferrin groups (219.92±22.99 nmol/g weight, 151.60±23.43 nmol/g weight, 158.16±12.33 nmol/g weight, respectively) in reducing brain MDA levels. In summary, all bovine lactoferrin groups (100, 200, and 400 mg/kgBW) significantly reduced brain MDA levels of SD rats in hyperlipidemia condition.